Broken gods: Collaborative filmmaking in troubled times. Issue 3 (26th May 2022) - Tilche, Alice
Abstract: Drawing on my involvement in the production of Broken Gods, a film that documents the growing participation of India's indigenous groups in projects of cultural erasure and conversion to Hinduism, this article reflects on the relations and tensions between a commitment to collaboration and critique. The film was co‐designed with indigenous communities, although such collaboration became impossible due to contrasting religious‐political affiliations. Collaborative techniques such as feedback resulted in challenging censorship claims that could only be resolved by reclaiming the importance of critique. Collaborative projects with nonanthropologists have often gone alongside a public or engaged anthropology, recasting ethnography as an act of citizenship with the potential to intervene in existing struggles (Lassiter 2005). Within these projects, anthropologists have traditionally taken the side of the oppressed. Yet, what happens when the marginal groups anthropologists traditionally championed align with the powerful forces anthropologists traditionally critiqued? How do we collaborate with groups we disagree with? And how do we represent disagreement in collaboration? The article approaches these questions via a consideration of methods, demonstrating how different media—and film, in particular—have different impacts on the possibilities and forms of both collaboration and critique. Resumen: Basado en mi involucramiento en la producción de Broken Gods, un filme que documenta la creciente participación de grupos indígenas de la India en proyectos de borrado cultural y conversión al hinduismo, este artículo reflexiona sobre las relaciones y tensiones entre un compromiso con la colaboración y con la crítica. El filme fue codiseñado con comunidades indígenas, aunque tal colaboración llegó a ser imposible debido a las contrastantes afiliaciones religioso‐políticas. Técnicas colaborativas tales como la retroalimentación resultaron en reclamaciones de censura que pudieron sólo ser resueltas al reivindicar la importancia de la crítica. Proyectos colaborativos con no antropólogos a menudo han ido junto a una antropología pública o comprometida, restructurando la etnografía como un acto de ciudadanía con el potencial de intervenir en luchas existentes (Lassiter 2005). Dentro de estos proyectos, los antropólogos tradicionalmente han tomado el lado de los oprimidos. Sin embargo, ¿qué sucede cuando los antropólogos de grupos marginales tradicionalmente defendidos se alinean con las fuerzas que los antropólogos criticaron tradicionalmente? ¿Cómo colaboramos con grupos con los que estamos en desacuerdo? ¿Y cómo representamos desacuerdos en colaboración? El artículo aproxima estas preguntas vía una consideración de métodos, demostrando cómo diferente media –y filme, en particular– tiene diferentes impactos sobre las posibilidades y formas tanto de colaboración como de crítica. [filmar, colaboración, crítica, indigeneidad] .